Dodges for Heterosexuality – Young Boys viewing Male Bodies in Pornography - Sørensen, Niels Ulrik (Kvinder, Køn & Forskning, 2008)
This article analyses young boys' descriptionsof their meetings with male bodies in pornography. It is based on qualitative interviews with 15 and 16 year old boys performed in the NIKK-project ";Youth, gender and pornography in the Nordic countries";, which took place in 2005 and 2006. The article explores the tension between the masculine and the feminine, the homosexual and the heterosexual generated during these meetings. Especially it focuses on the tension related to the young boys' attempts to assume masculine and heterosexual positions and the feminisation and homosexualisation inherent in their looking at male bodies in pornography. The article shows that the boys pursue various strategies to reinterpret body, gender and sexuality in order to avoid this feminisation and homosexualisation. However this reinterpretation sometimes creates friction between the masculine and the heterosexual, and the boys feel that they cannot position themselves as both - they have to choose between masculinity or heterosexuality. The article explores how and what they choose.